Effects of dietary garlic (Allium sativum) and papaya (Carica papaya) leaf powder on production performance, ruminal methanogen levels, gut parameters, and meat quality in goats - Qurrat-Ul-Ain; Imtiaz Rabbani; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Wasim Shehzad; Habib Rehman (Veterinary World)
Background and Aim: Several approaches have been employed to mitigate methane emissions from livestock, with varied results. This study evaluated the effects of shade-dried ground garlic leaf (GL) powder and papaya leaf (PL) powder as crop waste on feed intake, growth performance, ruminal microbial counts, gut epithelial barrier functions, and meat quality in goats.